1993
DOI: 10.1002/mpo.2950210115
|View full text |Cite
|
Sign up to set email alerts
|

Congenital juvenile chronic myelogenous leukemia: Therapeutic trial with interferon alpha‐2

Abstract: A newborn with congenital juvenile chronic myelogenous leukemia (JCML) is described. The diagnosis was suggested by the characteristic clinical and hematologic presentation, and was confirmed by the results of in-vitro cultures of the hematopoietic progenitors, which showed excessive proliferation of monocytic colonies, with and without the addition of exogenous granulocyte-macrophage colony stimulating factor (GM-CSF). Based on published in-vitro response of JCML cells to alpha interferon-2 (alpha IFN 2), we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1994
1994
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…(3) Interferon‐alpha has been noted to have some inhibitory effects on the spontaneous CFU‐GM growth in JMML (Estrov et al , 1987b). However, when applied to patients in a protocol using doses of interferon effective in ACML, no responses were observed (Maybee et al , 1993; Hazani et al , 1993). It is possible that other doses of interferon‐alpha would show some effectiveness in JMML.…”
Section: Prognosis Disease Course and Treatment Of Jmml And Monosomymentioning
confidence: 99%
“…(3) Interferon‐alpha has been noted to have some inhibitory effects on the spontaneous CFU‐GM growth in JMML (Estrov et al , 1987b). However, when applied to patients in a protocol using doses of interferon effective in ACML, no responses were observed (Maybee et al , 1993; Hazani et al , 1993). It is possible that other doses of interferon‐alpha would show some effectiveness in JMML.…”
Section: Prognosis Disease Course and Treatment Of Jmml And Monosomymentioning
confidence: 99%
“…IFN-␣ has been used as initial therapy in a small number of patients with JMML; responses were occasionally observed, though not as consistently as in CML. [4][5][6][7][8][9] Aricò et al 7 reported that five of seven patients with JMML, who received IFN-␣ with or without chemotherapy, remained alive. However, the patients in their study did not attain complete remission, but rather had stable disease.…”
Section: Discussionmentioning
confidence: 99%
“…Besides some nonresponses [22][23][24], several transient responses in vivo have been reported [1••,12,25]. A prospective study by the Pediatric Oncology Group with Intron-A (Schering-Plough, Kenilworth, NJ), 30,000 U/m 2 /d subcutaneously daily for 14 days, followed by the same dose three times weekly, was stopped for excessive toxicity [26].…”
Section: Interferon-αmentioning
confidence: 99%